A Case of Apocrine Sweat Gland Adenocarcinoma In A Tabby Cat - Doğan, Elif; Terzi, Funda; Kapçak, Ayşe (Harran Universitesi Veteriner Fakultesi Dergisi, 2021)
In this report, clinical, radiological, macroscopic and histopathological findings of apocrine sweat gland adenocarcinoma are presented in a 13-year-old male tabby cat. In clinical examination, soft tissue masses were detected in the caudal abdomen and left tuber coxae. Upon radiological examination, subcutaneous masses with the appearence of soft tissue contrast were detected and the masses were surgically removed under general anesthesia. The sizes of the masses were approximately 2x2x3 cm in the caudal abdomen and approximately 1x1x2 cm in the tuber coxae region. The cross-section of the mass was whitish-yellow in color. After the masses were fixed in 10% formaldehyde solution, a routine histopathology procedure was applied. In histopathological examination, apocrine sweat glands in a cystic structure and extensions from the center of the cyst to the lumen were determined, and anisonucleosis, anisocytosis and anaplastic cells with giant nuclei were observed in the epithelial cells of the gland facing the lumen. A diagnosis of papillary-cystic type apocrine sweat gland adenocarcinoma was made with these findings.
Keywords: Apokrin Karsinom; Kedi; Ter Bezi; Veterinary Surgery; Apocrine Carcinoma; Cat; Sweat Gland; Veteriner Cerrahi